2019
DOI: 10.14341/dm9735
|View full text |Cite
|
Sign up to set email alerts
|

Features the interaction of functional and metabolic remodeling of myocardium in comorbid course of ischemic heart disease and 2 type diabetes mellitus

Abstract: Background: Metabolic and structural changes in cardiomyocytes in diabetes mellitus lead to aggravation of contractile myocardial dysfunction in coronary heart disease (CHD). The contractility dysfunction of cardiomyocytes is determined by a change in the levels of sarcoplasmic reticulum (SR) Ca2+-ATPase and energetic supply of the cardiomyocytes. Aims: To study the features of functional remodeling of the heart muscle in coronary heart disease with and without type 2 diabetes mellitus (DM2) depend on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
1
0
4
Order By: Relevance
“…This probably provides better functionality of SPR and improves the contractile function of the myocardium, even at the level of the whole heart. This conclusion does not contradict our previously published findings, obtained in comparative study of contractile function of heart muscle in CHD without comorbidity and CHD associated with T2DM [2,5].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…This probably provides better functionality of SPR and improves the contractile function of the myocardium, even at the level of the whole heart. This conclusion does not contradict our previously published findings, obtained in comparative study of contractile function of heart muscle in CHD without comorbidity and CHD associated with T2DM [2,5].…”
Section: Resultssupporting
confidence: 78%
“…The cohort study VALIANT has showed that T2DM is an independent predictor of unfavorable coronary events during the first year after myocardial infarction or patient death [4]. Our previous studies showed that CHD and T2DM comorbidity significantly affects cardiac remodeling at the cellular and molecular levels [1,2,5]. The combined influence of ischemic and diabetic/hyperglycemic factors on the cardiac muscle was also demonstrated in biologic models and in patients with comorbidity.…”
mentioning
confidence: 96%
“…Помимо прямого повреждающего действия и опосредованного, через активизацию прооксидантной системы в основе вибрационно-опосредованных изменений лежат нейрогуморальные [8,[16][17][18][19] и нейрорефлекторные нарушения [20,21], усугубляющие гипоксию тканей [7]. У пациентов с ВБ наблюдаются изменения кальциевого гомеостаза, который находится под контролем глюкокортикоидов, соматотропина, кальцийрегулирующих гормонов (паратгормон, кальцитонин) и витамина D [22].…”
Section: патофизиологические предпосылки ремоделирования миокарда на ...unclassified
“…Набор пациентов проводился в течение 2017-2018 гг. Настоящее исследование включает часть данных, использованных в предыдущей работе [15] Описание медицинского вмешательства Всем пациентам на этапе подготовки к операции коронарного шунтирования проводили обязательные инструментальные и лабораторные обследования. Они включали эхокардиографию сердца и сосудов, а также определение в крови HbA 1c .…”
Section: продолжительность исследованияunclassified
“…Оценивали величину экстрасистолического (ЭС) и постэкстрасистолического (ПЭС) инотропного ответа мышц, которую выражали в процентах к амплитуде регулярного цикла. Этот подход используют для оценки внутриклеточного гомеостаза ионов кальция [15].…”
Section: методы регистрации исходовunclassified